Does forest loss affect the communities of trap-nesting wasps (Hymenoptera: Aculeata) in forests? Landscape vs. local habitat conditions - Taki, Hisatomo; Viana, Blandina F; Kevan, Peter G; Silva, Fabiana O; Buck, Matthias (Journal of insect conservation, 2008)
We investigated changes in the communities of trap-nesting Hymenoptera in forests in relation to forest loss on a landscape scale and understory conditions on a local habitat scale. Two specific questions were addressed. (1) Do the communities change with degrees of forest loss? (2) Do the communities change with varying local environmental conditions of understory habitats? The study was made in a landscape characterized by distributed forest patches within intensively managed agricultural surroundings. We deployed trap-nests at eight randomly selected sites in forests in summer. To quantify forest loss, the amount of forest coverage was calculated using GIS. To indicate local habitat conditions, the species richness of understory flowering plants was used. All together, 12 species of wasps and no bees were captured. Regression analyses showed that both abundance and species richness of the wasps were not significantly related to forest coverage. However, abundance of trap-nesting wasps was significantly related to species richness of understory plants, but species richness of the wasps was not significantly related to the plants. These results suggest that communities of trap-nesting wasps in forests are influenced more by the local habitat conditions than by forest loss.